Prevalence of Dental Caries among the Population of Gwalior (India) in Relation of Different Associated Factors - Khan, Abdul Arif; Jain, Sudhir K.; Shrivastav, Archana (European Journal of Dentistry, 2008)
Objectives: India is unique in entire world due to variety of dietary habits in population. Many people of India follow totally vegetarian life style through their entire life time due to some religious and cultural reasons. Present study tried to analyze the role of different factors in the occurrence of dental caries including dietary habit.Methods: Persons suffering with dental caries were examined for the type of dental cariesin relation to different factors. Dental examination was performed and patients were asked a questionnaire andthe data was recorded and analyzed.Results: Incidence of dental caries was higher in female. High number of dental caries patients was observed among vegetarian population. 21-30 year age group was found to be most infected with dental caries.Conclusions: This study can be helpful to analyze respective role of different dietary factors including protein rich diet, age, gender etc. on the prevalence of dental caries, which can be helpful to counteract the potential increase in the cases of dental caries and to design and plan preventive strategies for the persons at greatest risk. (Eur J Dent 2008;2:81-85)
Keywords: Dental caries; Periodontitis; Orodental; Dietary habit; Saliva